Continuous Exposure to Non-Soluble β-Glucans Induces Trained Immunity in M-CSF-Differentiated Macrophages - Moerings, Bart G. J.; de Graaff, Priscilla; Furber, Matthew; Witkamp, Renger F.; Debets, Reno; Mes, Jurriaan J.; van Bergenhenegouwen, Jeroen; Govers, Coen (Frontiers in Immunology, 2021)
Beta-glucans enable functional reprogramming of innate immune cells, a process defined as “trained immunity”, which results in enhanced host responsiveness against primary (training) and/or secondary infections (resilience). Trained immunity holds great promise for promoting immune responses in groups that are at risk (e.g. elderly and patients). In this study, we modified an existing in vitro model for trained immunity by actively inducing monocyte-to-macrophage differentiation using M-CSF and applying continuous exposure. This model reflects mucosal exposure to β-glucans and was used to study the training effects of a variety of soluble or non-soluble β-glucans derived from different sources including oat, mushrooms and yeast. In addition, trained immunity effects were related to pattern recognition receptor usage, to which end, we analyzed β-glucan-mediated dectin-1 activation. We demonstrated that β-glucans, with different sources and solubilities, induced training and/or resilience effects. Notably, trained immunity significantly correlated with dectin-1 receptor activation, yet dectin-1 receptor activation did not perform as a sole predictor for β-glucan-mediated trained immunity. The model, as validated in this study, adds on to the existing in vitro model by specifically investigating macrophage responses and can be applied to select non-digestible dietary polysaccharides and other components for their potential to induce trained immunity.